2022
DOI: 10.3389/fbioe.2022.874931
|View full text |Cite
|
Sign up to set email alerts
|

Customized Design 3D Printed PLGA/Calcium Sulfate Scaffold Enhances Mechanical and Biological Properties for Bone Regeneration

Abstract: Polylactic glycolic acid copolymer (PLGA) has been widely used in tissue engineering due to its good biocompatibility and degradation properties. However, the mismatched mechanical and unsatisfactory biological properties of PLGA limit further application in bone tissue engineering. Calcium sulfate (CaSO4) is one of the most promising bone repair materials due to its non-immunogenicity, well biocompatibility, and excellent bone conductivity. In this study, aiming at the shortcomings of activity-lack and low me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The decay of biomaterials containing Ca 2+ generates a localized, calcium-abundant microenvironment that has been employed as a catalyst for wound healing and/or as an osteoinductive substance. [ 37 , 38 , 39 , 40 ]. Moreover, the generation of reactive oxygen species [ 41 , 42 , 43 ] and their application in antimicrobial dental therapy [ 44 , 45 , 46 ], as well as the use of CaO 2 for environmental purposes have been widely reported [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decay of biomaterials containing Ca 2+ generates a localized, calcium-abundant microenvironment that has been employed as a catalyst for wound healing and/or as an osteoinductive substance. [ 37 , 38 , 39 , 40 ]. Moreover, the generation of reactive oxygen species [ 41 , 42 , 43 ] and their application in antimicrobial dental therapy [ 44 , 45 , 46 ], as well as the use of CaO 2 for environmental purposes have been widely reported [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polylactic acid (PLA), polycaprolactone (PCL), and poly lactic-co-glycolic acid (PLGA) are representative synthetic polymers that have been prepared to obtain a variety of scaffold materials. 129,130 PCL is an aliphatic and semi-crystalline polymer that displays remarkable toughness and mechanical strength, and it exhibits sufficient biocompatibility. However, its degradation products may contribute to the spread of degradation rates and inflammatory responses.…”
Section: Synthetic Polymermentioning
confidence: 99%
“…However, their mechanical and processing properties provide notable benefits. Polylactic acid (PLA), polycaprolactone (PCL), and poly lactic‐co‐glycolic acid (PLGA) are representative synthetic polymers that have been prepared to obtain a variety of scaffold materials 129,130 …”
Section: Biomaterials For Tissue Defectsmentioning
confidence: 99%
“…So, it is considered as one of the most promising materials for bone defect repair. In our previous study (Liu et al, 2022), we synthesized the PLGA/CaSO 4 scaffolds 3D-printed scaffolds (PC) with different ratios, and found that the incorporation of CaSO 4 with 20% wt in PLGA not only improved the mechanical properties of the scaffold but also enhanced its in vitro osteogenic effect (Liu et al, 2022), demonstrating that it is a promising material for bone repair. However, it is difficult to achieve sufficient bone defect repair with a single functional scaffold.…”
mentioning
confidence: 99%
“…PLGA and CaSO 4 (20 wt% of the quality of PLGA) powder were added into the beaker and then stirred evenly at 200°C. The mixture was then injected into the 3D printer and the scaffold was printed according to the set parameters of the previous study (Liu et al, 2022). The nozzle temperature was 180 °C, and the temperature of supporting substrates during FDM printing was 120 °C.…”
mentioning
confidence: 99%